Promoção da segurança do paciente pelo enfermeiro na Atenção Primaria à Saúde - Cunha, Karine Cristina Siqueira (2023)
"It is known that healthcare, paradoxically, can also result in harm to patients when errors and adverse events occur. Thus, patient safety is a global concern in all healthcare facilities, including those in Primary Health Care, considered the entry point into the healthcare system and responsible for the continuous coordination of services with a focus on the population. This study aims to analyze the promotion of patient safety based on the experiences of nurses working in Primary Health Care. It is an exploratory and descriptive study with a qualitative approach, following the theoretical and methodological framework of Dialectical Hermeneutics, conducted with 24 nurses working in Primary Health Care, who were selected through the snowball sampling technique. It was developed in a virtual environment through the Skype platform, and data collection consisted of a single interview per participant. These interviews were guided by an instrument developed by the authors, consisting of a questionnaire for the sociodemographic and professional characterization of the participants and a semi-structured interview script composed of three open-ended questions. The interviews were recorded and later transcribed. Descriptive statistics and presentation in tables were used for the presentation of data from sociodemographic and professional characterization, and thematic reflective analysis was used for the organization and analysis of data from the semi-structured interview. The Human Error Theory and dialectical hermeneutics were adopted as theoretical and methodological references, respectively. Approval was obtained from the Research Ethics Committee, under opinion no. 5,582,486. Twenty-four nurses participated, with a predominance of females, single, aged 30 to 40 years, working in the Family Health Strategy, with a work experience in Primary Health Care of up to 5 years, mostly concentrated in the state of Minas Gerais. Four themes were defined: 'Patient safety in Primary Health Care: an incipient theme compared to the hospital,' 'Latent conditions: risks to patient safety in Primary Health Care,' 'Active failures: risks to patient safety in Primary Health Care,' and 'Promotion of patient safety: actions by nurses to interpose barriers to errors and adverse events.' It was apprehended from this study that patient safety is still an incipient theme that needs further exploration and investment in the thematic area. Nurses identify latent conditions and active failures that can represent risks and, thus, undertake corresponding actions to promote patient safety, even though they do not cover all the mentioned situations. The study may contribute to the literature, which still focuses more significantly on the hospital setting, by raising awareness among professionals working in these units regarding the identification of possible risks and the need to implement actions that constitute barriers to the occurrence of adverse events. It may also advocate for Primary Health Care to be considered a priority by managers and policymakers when aiming for safe healthcare." Keywords: patient safety; primary health care; nursing